Impact of Subsidies and Socioeconomic Status on Varicella Vaccination in Greater Tokyo, Japan - Nagaoka, Kei; Fujiwara, Takeo (Frontiers in Pediatrics, 2016)
Background: Although the control of varicella outbreaks is an important health issue, cost could present a major barrier for vaccination The aim of this study is to investigate the association of vaccine subsidies and caregivers’ socioeconomic status with varicella vaccine coverage of their children in Greater Tokyo, Japan, before the period that varicella vaccination was included as routine immunization program. Methods: Participants were recruited from two different cities. In Chiba city, parents of 18-month-old infants (N = 378) undergoing a medical examination in July 2013 were recruited at a clinic where no subsidy for varicella immunization was provided. In Nishitokyo city, parents of 24- to 30-month-old children (N=315) undergoing a health check-up in July and August 2013 were recruited at a clinic where a partial subsidy was provided. The association between household income and varicella immunization was investigated by multivariate logistic regression stratified by city. Results: Vaccine coverage was 61.0% in Chiba city and 73.3% in Nishitokyo city. In Chiba city, odds ratios of middle and high household income for varicella immunization were 4.22 (95% CI (confidence interval): 1.65-10.7) and 5.94 (95% CI: 1.89-18.6) compared to low household income, respectively. However, household income was not associated with varicella vaccination in Nishitokyo city. Neither working status nor education was associated with vaccination in both cities. Conclusions: While household income was associated with high vaccine coverage in the city with no vaccine subsidy, this association was not observed in the city where the subsidy was given, which suggests that cost is a barrier for varicella immunization.Thus, in countries where varicella vaccination is not included in routine immunization program, introducing subsidies nationwide or routine immunization programs for varicella vaccination would be an important approach to eliminate inequality in vaccine coverage.